Best Practices of Human Rights in a Democratic Country - Guragain, Govinda Prasad (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2023)
This article has displayed the state of human rights practices and provisions in a democratic nation, Nepal. Democracy, progress, the rule of law, and the preservation of human rights and fundamental freedoms are all inextricably linked and mutually reinforcing. Nepal, being a democratic nation hence ensures human rights to its citizen. From the past few decades to the present date, a number of progresses have been made in the practices and provisions. The backward and underprivileged groups have been rendered their rights in accordance with the 2015 Constitution. Nevertheless, the Nepalese government has continuously neglected the Commission's recommendations to examine and prosecute human rights violations in accordance with the obligations of the Constitution. The government of Nepal should focus on the human rights movement which is also facing enormous difficulties from numerous activities that contravene the essential spirit of the constitution, democratic norms, and the Universal Declaration of Human Rights. This paper has presented the progression in human rights provisions and practices and even made suggestions to be more proactive in ratifying the Rome Statute as soon as feasible in order to improve Nepal’s international image.